2016
DOI: 10.1245/s10434-016-5325-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Segmental Mastectomy and Excisional Biopsy Using Hydrogel-Encapsulated Clip Localization as an Alternative to Wire Localization

Abstract: Intraoperative ultrasound-guided excision of nonpalpable breast lesions using a hydrogel-encapsulated biopsy clip for breast conserving therapy is a safe and feasible alternative to the traditional preoperative wire localized excision. This technique will lead to improvement in patient experience, operative efficiency, and alleviate wire-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…HER2-positive and triple-negative breast cancers are associated with early events, but luminal cancers (the majority of cases in this series) are more frequently late-recurring, thus possible recurrences may be missed in the present study. 26 No differences were observed in surgery time between ROLL and TCC (respectively, 65 vs 62.9 minutes) despite operative time 34,35 Most of the previous studies were designed before the recent definition of adequate margins for invasive cancer and DCIS, and frequently patients with benign or uncertain lesions were included, conversely to the present study. 8,[27][28][29][30][31][32][33] Furthermore, adequacy of resection has been often evaluated on specimen volumes or weight, kind of studies since adequacy of resection is the main end-point for breast-conserving surgery of nonpalpable cancers, and current imprecisions and heterogeneity in volumes measurement have led to inconsistent or controversial results.…”
Section: Mass-like Lesions Such As Nodules or Distortions Have Been Omentioning
confidence: 78%
See 1 more Smart Citation
“…HER2-positive and triple-negative breast cancers are associated with early events, but luminal cancers (the majority of cases in this series) are more frequently late-recurring, thus possible recurrences may be missed in the present study. 26 No differences were observed in surgery time between ROLL and TCC (respectively, 65 vs 62.9 minutes) despite operative time 34,35 Most of the previous studies were designed before the recent definition of adequate margins for invasive cancer and DCIS, and frequently patients with benign or uncertain lesions were included, conversely to the present study. 8,[27][28][29][30][31][32][33] Furthermore, adequacy of resection has been often evaluated on specimen volumes or weight, kind of studies since adequacy of resection is the main end-point for breast-conserving surgery of nonpalpable cancers, and current imprecisions and heterogeneity in volumes measurement have led to inconsistent or controversial results.…”
Section: Mass-like Lesions Such As Nodules or Distortions Have Been Omentioning
confidence: 78%
“…Both WGL and RSL have well known drawbacks, such as displacement, fracture or patient's discomfort in case of WGL, and an additional procedure before surgery to insert the seed, as well as radioactivity handling and disposal concerns, in case of RSL . Only a few studies have evaluated US localization of clip markers, providing encouraging results compared with WGL; however, an accurate assessment of such technique in terms of adequacy of resection volumes specifically in different lesion types is still lacking, especially compared with ROLL …”
Section: Discussionmentioning
confidence: 99%
“…With improved clip visibility on ultrasound, the clipped nodes could be excised in a similar fashion as nonpalpable clipped breast lesions using ultrasound guidance alone. 7 In fact, intraoperative ultrasound-guided excision of axillary clipped node post-NACT had been reported to be feasible and safe. 19 In our case however, we advocated a multidisciplinary approach of the radiologists preoperatively placing a skin mark to further delineate the location of the clip more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have looked at use of UVCs—more specifically, the HydroMARK clip—with US‐guided PMs . These studies found the HydroMARK clip to be an overall safe, efficient, and effective alternative to wire localization when used with US guidance for excision of early‐stage breast cancer.…”
Section: Discussionmentioning
confidence: 99%